Analyzing short-run and long-run causal relationships between energy consumption, CO2 emissions, and business performance in the hospitality industry - Stojanović Vojislav; Radivojević Nikola; Owen Abdallah M.; Jahić Adnan; Đorđević Darko (Ekonomija: teorija i praksa)
This paper explores the long-term and short-term relationships between hotel business performance, energy consumption, and CO₂ emissions by applying the Vector Error Correction Model (VECM), the VEC Granger causality test, and the block exogeneity Wald test. The study is based on a sample of 121 hotels over the period from 2015 to 2024. The results reveal a strong and statistically significant long-run relationship among the examined variables. The findings suggest that when deviations from long-run equilibrium occur-such as when hotel performance diverges from a sustainable level due to excessive energy consumption or increased CO₂ emissions-the system tends to self-correct over time. This adjustment mechanism implies that unsustainable practices eventually lead to operational setbacks, pushing performance back toward its long-term path. The results also indicate a unidirectional short-run causal relationship between hotel business performance and energy consumption, as well as a bidirectional causality between business performance and CO₂ emissions.